Rheumatoid arthritis disease activity and adverse events in patients receiving tofacitinib or tumor necrosis factor inhibitors: a post hoc analysis of ORAL Surveillance - Karpouzas, George A.; Szekanecz, Zoltán; Baecklund, Eva; Mikuls, Ted R.; Bhatt, Deepak L.; Wang, Cunshan; Sawyerr, Gosford A.; Chen, Yan; Menon, Sujatha; Connell, Carol A.; Ytterberg, Steven R.; Mortezavi, Mahta (Therapeutic advances in musculoskeletal disease, 2023)
Background: In patients with rheumatoid arthritis (RA), persistent inflammation and increasing disease activity are associated with increased risk of adverse events (AEs). Objectives: To assess relationships between RA disease activity and AEs of interest in patients treated with tofacitinib or tumor necrosis factor inhibitors (TNFi). Design: This was a post hoc analysis of a long-term, postauthorization safety endpoint trial of tofacitinib versus TNFi. Methods: In ORAL Surveillance, 4362 patients aged ⩾50 years with active RA despite methotrexate, and ⩾1 additional cardiovascular (CV) risk factor, were randomized 1:1:1 to tofacitinib 5 or 10 mg twice daily or TNFi for up to 72 months. Post hoc time-dependent multivariable Cox analysis evaluated the relationships between disease activity [Clinical Disease Activity Index (CDAI)], inflammation [C-reactive protein (CRP)], and AEs of interest. The AEs included major adverse CV events (MACE), malignancies excluding nonmelanoma skin cancer (NMSC), venous thromboembolism (VTE), serious infections, herpes zoster (HZ), nonserious infections excluding HZ (NSI), and death. Results: Across treatments, risk for NSI was higher when patients had CDAI-defined active disease versus remission; MACE and VTE risks trended higher, but did not reach significance. Hazard ratios for MACE, malignancies excluding NMSC, VTE, infections, and death rose by 2–9% for each 5-mg/L increment in serum CRP. The interaction terms evaluating the impact of treatment assignment on the relationship between disease activity and AEs were all p > 0.05. Conclusion: In ORAL Surveillance, higher NSI risk was observed in the presence of active RA versus remission. The risk of MACE and VTE directionally increased in active disease versus remission, although statistical power was limited due to small event numbers in these categories. The relationship between active disease and AEs was not impacted by treatment with tofacitinib versus TNFi. Registration: NCT02092467. Plain language summary The link between disease activity and adverse medical events in people with rheumatoid arthritis taking tofacitinib or tumor necrosis factor inhibitors. Why was the study done? • People with rheumatoid arthritis (RA) who have uncontrolled symptoms (high disease activity) have a higher chance of having adverse medical events (medical problems that occur during treatment with a medication) than people who have mild symptoms (low disease activity). • We looked at the link between levels of disease activity and the risk of having adverse medical events in people with RA who took tofacitinib or a tumor necrosis factor inhibitor (TNFi) medication. What did the researchers do? • We used the results of ORAL Surveillance, a long-term safety trial in people with RA. ○ In this study, people with RA were 50 years or older and at high risk of a major cardiovascular event such as heart attack or stroke. • For up to 6 years, people took tofacitinib 5 or 10mg tablets two times a day or TNFi injections. • We used statistical tests to examine the link between different levels of RA disease activity or inflammation and different adverse medical events, such as: ○ major cardiovascular events (such as heart attack, stroke, or death due to heart failure) ○ cancers ○ blood clots ○ infections ○ deaths. What did the researchers find? • In people who took tofacitinib or TNFi: ○ People with active disease (those with RA symptoms) had a higher risk of infections that did not lead to hospitalization (nonserious infections) than people in remission (those with very mild symptoms or no symptoms at all). ○ People with active disease also had a slightly higher risk of major cardiovascular events and blood clots than those in remission. ○ Higher levels of inflammation led to increased risk of major cardiovascular events, cancers, blood clots, infections, and deaths. What do the findings mean? • Active RA disease leads to higher risk of adverse medical events. • The medication used (tofacitinib or TNFi) did not affect the link between levels of RA disease activity and adverse medical events. • This study was limited by the low number of adverse medical events recorded.